Local language programs in cultural radios to maintain Indonesian national identity - Wahyuningtyas, Dwi; Kusuma, Ade; Febrianita, Roziana; Achmad, Zainal Abidin (Department of Anthropology, Faculty of Social and Political Sciences, Hasanuddin University., 2021)
Private radio, which relies on programs with local cultural content in local languages, affects the success of reaching large audiences and financial benefits. In East Java, four private radios have the advantage of local cultural programs, namely Radio Jodhipati FM in Nganjuk, Radio Sritanjung FM in Banyuwangi, Radio Nada FM Sumenep, and Radio Media FM in Surabaya. This study aims to determine what cultural programs can increase the number of listeners and profitability on the four cultural radios. Furthermore, to find out why listeners like local cultural programs of each radio. This research on broadcast content on four cultural radios uses virtual ethnographic methods by collecting data, both offline and online. Researchers are involved in broadcasting activities on four cultural radios (offline) and listener interaction activities in the virtual world (online), namely Facebook and WhatsApp. This study conducted interviews with twelve informants representing radio management, local cultural figures, and loyal listeners. The results showed that each radio has excellent cultural programs with a solid appeal to maintain listener loyalty. The four cultural radios involve cultural experts in designing cultural programs. Listeners try to maintain local tastes because they realize that love for local culture is a strengthening of national identity, which is the richness of Indonesian culture.